Faktor Yang Mempengaruhi Auditor Switching Pada Sektor Industri Barang Konsumsi Di BEI Tahun 2017-2020 - Dewi Larasati; Suhesti Ningsih; Wikan Budi Utami (Jurnal Ilmiah Keuangan Akuntansi Bisnis (JIKAB), 2023)
The purpose of this research was to prove and analyze the empirical evidence of factors that have influenced on auditor switching in manufacturing companies in the consumer goods industry sector listed on the Bursa Efek Indonesia (BEI) on periode 2017 – 2020. Variables being used on this reseacrh were audit delay, KAP size, and management change. The sampling method used is the purposive sampling method. Samples of this reseach was 19 companies in consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) on 2017-2020. The sampling method used is purposive sampling method. The research sample was 19 companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2017-2020 so that in a 4 yearperiod a sample of 76 companies was obtained. The data analysis method used is descriptive statistical analysis and classical assumption test analysis. To test the hypothesis using multiple linear regression analysis, F test, t-test and the coefficient of determination test. Based on the results of data processing using the F test method, it is knwon that audit delay, KAP size and management change simultaneously affect auditor switching. Meanwhile, based on the results of the t-test processing, it is known that audit delay has no significant efferct on auditor switching, while the size of KAP and management turnover has a significant effect on auditor switching.